The “AI Mode”: How Food Delivery Riders in the Netherlands and South Korea Experience Algorithmic Management - Seonok Lee (Italian Labour Law e-Journal)
This study investigates the complex dynamics between algorithmic management and worker agency, focusing on food delivery riders in the Netherlands and South Korea. A combination of digital observation, semi-structured interviews, and personal work experience is utilised to examine how platforms like Thuisbezorgd, Uber Eats, Bamin, and Coupang Eats use algorithmic tools, penalties, and incentives, to control labour. Findings highlight that algorithmic management impacts riders’ autonomy, income stability, safety, and working conditions, often creating dependency on the platform while restricting upward mobility. Riders exhibit diverse responses: younger part-time workers approach AI-driven systems with curiosity, while many full-time self-employed riders express frustration over diminished autonomy and precarious working conditions. Additionally, the study highlights the symbolic importance of features such as the “accept or decline” option, which provides riders with a semblance of autonomy and control. While these features are often more symbolic than substantive, they allow riders to construct a narrative of self-reliance and dignity within a system characterised by pervasive control. The research underscores the need to understand the intricate interplay between algorithmic management and worker agency in the platform economy.